Potensi Pengembangan Ekowisata Pada Kawasan Objek Wisata Alam Batu Jato Di Kecamatan Nanga Taman Kabupaten Sekadau - Maljani Putri, Yosefin Dinda; Sirojul Munir, Achmad Mulyadi; Ruliyansyah, Agus (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
The Potential of Developing Ecotourism in the Batu Jato Natural Tourism Area in the Nanga Taman District, Sekadau Regency. Batu Jato is one of the natural tourist destinations located in Pantok Village, Nanga Taman District, Sekadau Regency, West Kalimantan. Batu Jato has the potential of an area that is feasible to develop as an ecotourism area. The purpose of this study was to analyze the potential of the Batu Jato tourist attraction area to be developed as an ecotourism area. This research was conducted from June 2022 to September 2022 in the Batu Jato area. The method used in this research is the Purposive Sampling method. Based on the results of the research, the Jato stone tourism area has a variety of very interesting potentials, some of which are: beautiful landscapes, biological resources of flora and fauna, religious tourism sites, and community culture. Based on the results of the IKW calculation at each research station, the camping/outbound tourism category is included in the unsuitable category, while the sitting tour is included in the suitable category. The results of the DDK calculation at each station show that the maximum number of visitors is 253 people / day. The SWOT analysis diagram shows that internal and external factors are in Quadrant I, which creates a strategy that uses strengths to take advantage of existing opportunities.zzz